The way of peace : A.J. Muste's writings for the church - Muste, A. J. (Abraham John), 1885-1967 (Wipf and Stock Publishers, 2016)
One of the most influential social activists of the twentieth century, A.J. Muste is remembered by some as a pioneering labor leader, by others for his work helping lay the foundations of the civil rights movement, and by many others for his tireless work for peace, justice, economic equality, and the protection of civil liberties. As a pastor, Muste's life and work were shaped by his Christian theology. This collection of Muste's sermons, speeches, articles, and other works for religious audiences is a timely call for Christians to follow him in the way of peace.